ANALYZING AND PRICE FORECASTING FOR SELECTED GRAIN CLASSIFIED AS BIOMASS FEEDSTOCK ON THE EU MARKETS - Michal Kolcun; Beata Rusek; Frantisek Janicek; Daniela Spirkova (European Scientific Journal, ESJ, 2014)
The paper deals with the price trends of biomass feedstock used as renewable energy sources. Special attention is paid to kind of grain classified as the particular sort of biomass in Poland. The comparative prices analysis of some selected kind of grain on the markets of the EU countries is presented in this paper. Also there was demonstrated validity of two forecast models in order to forecast the prices for one month. After the forecasting, the accuracy was evaluated as well as the validation forecasts allowing for evaluation.